Bioativador no desempenho fisiológico de sementes de cenoura - Almeida, Andréia da Silva (2008)
Bioactivators are complex organic substances which modify plant growth. Two insecticides have shown this effect, aldicarb and thiametoxan. The insecticide thiametoxan activates several physiological reactions, such as protein expression. These proteins interact with several defense mechanisms, allowing the plant to better withstand adverse environmental conditions. The objective of this work was to evaluate the influence of this bioactivator on the physiological performance of carrot seeds. Seeds of two cultivars, Brasília and Brazlândia, were assessed, each represented by four lots. The seeds were treated with three concentrations of both insecticides: 0,0 mL, 0,05 mL and 0,4 mL/l. The evaluation of the physiological quality of seeds was performed through the following tests (developed under conditions of presence and absence of water stress): germination, first germination count, accelerated aging, root length, germination under glasshouse environment. Thiametoxan stimulated the physiological performance of seeds, regardless of the water status. Concentrations of 0,05 and 0,4 mL showed good efficiency, however, a trend was observed for the highest concentration to promote larger increments in the seed quality of both cultivars.